Port mortuary - Cornwell, Patricia Daniels (New York : G.P. Putnam's Sons, 2010)
When Scarpetta examines a young man's body, she discovers stunning indications that he may have been alive when he was zipped inside a pouch and locked insider the cooler of her new Cambridge Forensic Center in Massachusetts.
Keywords: United States. -- Dept. of Defense -- Fiction; Scarpetta, Kay (Fictitious character) -- Fiction; Medical examiners (Law) -- Fiction; Forensic pathologists -- Fiction; Women physicians -- Fiction; Terrorism -- Prevention -- Fiction; Cambridge (Mass.) -- Fiction